Synthesis and Characterization of Paramomycin-loaded CoFe2O4/Polyethylene Glycol – Poly (Lactic-co-glycolic Acid) Core-Shell Spheres for Treatment of Cutaneous Leishmaniasis. Issue 3 (4th March 2022) - Jafari, Maral; Nourbakhsh, Mohammad Sadegh; Salati, Amir; Farrokhi, Amir Salek
Abstract: Cobalt ferrite (CoFe2 O4 ) nanoparticles were successfully synthesized using two calcination methods and characterized by X-Ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FE-SEM), Fourier Transform Infrared spectroscopy (FTIR), and Vibrating-Sample Magnetometry (VSM). The microwaved ferrite cobalt nanoparticles were coated by PLGA-PEG by a double emulsion method with and without paromomycin drug. The FTIR and XRD results revealed the spinel structure of CoFe2 O4 without any impurity. However, the nanoparticle crystallite sizes of the microwave calcined CoFe2 O4 were smaller than those of the electrical furnace calcined CoFe2 O4 . The VSM analysis confirmed the magnetic properties of CoFe2 O4 with an acceptable saturated magnetization and coercivity. The use of PLGA-PEG coating had a significant effect on the crystallite size and magnetic properties of the designed formulation. Finally, the anti-leishmanial activity of the new formulation was found to be∼52% more than that of the effect of the pure drug on promastigotes. This phenomenon demonstrated that the paromomycin-loaded magnetic nanoparticles (NP@PEG-PLGA/PM) sample has a greater effect on preventing the survival of parasites.